Efectos del ejercicio aeróbico en la composición corporal, resistencia cardiovascular, ciclo circadiano, síndrome T3 Polar en la primera misión de Colombia a la Antártida - Castro Herrera, Juan Miguel (2017)
In the austral summer 2014-2015 was developed Colombia's first expedition to Antarctica in order to be consultative country in the Antarctic Treaty System, the Colombian Air Force was linked to a project in Health Sciences pretending determine cardiorespiratory physiological changes, body composition, Polar T3 Syndrome and quality of sleep that occur in acute extreme cold acclimation in a group of explorers of Antarctica, with aerobic exercise for 4 weeks of training. Were valued in Colombia and in Antarctica 36 subjects were randomly divided into two groups, one performed exercise and a sedentary, we applied the clinical index of Zulewsky, Epworth scale, the questionnaire Pittsburg, maximum oxygen consumption and composition bodily. Of the 36 subjects 80% are men and only 20% are women and have an average age of 33.5 years, who exercised decreased 4% BMI, decreased 30% chance of developing hypothyroidism, 48% improved sleep quality, 51% decreased the likelihood of daytime sleepiness and increased 7% maximum oxygen consumption. Increase control sedentary group 10% fat and 10% decreased cardiovascular fitness. Exercise is a protective mechanism in exposure to extreme temperatures and decreases the likelihood of developing metabolic and cardiovascular diseases. More sedentary lifestyle cold end functions facilitating rapidly deteriorating disease of any kind. No verão austral 2014-2015 foi desenvolvido primeira expedição da Colômbia para a Antártida a fim de ser país consultivo no Sistema do Tratado Antártico, a Força Aérea Colombiana foi vinculado a um projeto em Ciências da Saúde fingindo determinar alterações fisiológicas cardiorrespiratórias, composição corporal, síndrome T3 Polar e qualidade do sono que ocorrem na aclimatação frio extremo aguda em um grupo de exploradores da Antártida, com o exercício aeróbio durante 4 semanas entrenamiento. Foram valorizados na Colômbia e Antarctica 36 indivíduos foram divididos aleatoriamente em dois grupos, um exercício e executar outras índice clínico sedentária, eles ...